Greenland, Kejser Franz Joseph Fjord and Nordenskiöld Gletscher annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
July 29, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. On left; Riddarborgen (Peak). S.W. point at entrance to Kjerulfs [Kjerulf] Fjord. On right: extreme inner end of Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord], show [shows] Nordenskjold Glacier [Nordenskiöld Gletscher], filling extreme inner end of Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. Photo looking west from S.S. Veslekari. This is No. 5 in pan B.